A Systematic Review of Teachers’ Teaching Styles and Their Impact on EFL Student Learning Outcomes - Almira, Nahdah Fitri; Almira, Zaidah Fitri; Vircavani, Catur; Agustina, Eliasanti (Universitas PGRI Adi Buana Surabaya, 2025)
In the field of English as a Foreign Language (EFL), teaching style is a crucial factor influencing students' motivation and engagement. However, because there are more separate studies than comprehensive syntheses, there remains a deficiency in the overall synthesis of what is commonly utilized and, from the perspective of learners, the most effective in teaching. This systematic review seeks to determine prevalent teaching styles in EFL classrooms and their perceived effects on students' engagement and motivation. Employing the SALSA framework—Search, Appraisal, Synthesis, and Analysis—30 peer-reviewed empirical studies from 2014 to 2024 were analyzed. Studies were chosen based on stringent inclusion criteria, including EFL/ELT environments and empirical data on teaching approaches linked to student results. Findings indicate that student-centered approaches, especially the Facilitator and Delegator styles, consistently correlate with enhanced learner autonomy, emotional backing, and active engagement. Traditional approaches like Expert and Formal Authority styles, although still in use, are shown to hinder intrinsic motivation when they are overly dominant. Moreover, contextual elements like culture, type of institution, and mode of learning (for instance, in-person or online) greatly influence the success of teaching methods. Although they are valuable, the majority of research depends on limited, perception-driven data with a narrow geographic focus and insufficient attention to young learners or informal education. Future studies must tackle these constraints using longitudinal and experimental methodologies. The review underscores the critical significance of culturally relevant and adaptive teaching methods in enhancing EFL learning results.